Strategic Choice: an examination of the Chinese luxury market for the Mantero Company - Lin, Weibiao (2007)
The ultimate objective of strategic management is to instruct managers in how to gain sustained competitive advantage within a dynamic market environment. The Chinese luxury market, with its extremely dynamic nature, provides a strong insight for the application of the dynamic business strategy theory. Relatively, by using a dynamic market view to apply the Porter's generic strategies, the dissertation aims to provide a detailed business strategic plan for Mantero Company. Research on the Chinese consumer's consumption behavior is conducted and tested based on the age and geographic difference. The research mainly analyzes two age groups, one is consumers aged from 25 to 45 years old, and another is consumers aged from 55 to 70 years old. Consumers from the four regions of China are analyzed, which are Guangzhou, representing the southern China, Shanghai, representing the east China, Beijing, representing the northern China, and Chongqing, representing the central China. Based on the analysis, a potential demand for luxury goods in China is identified and justified, which is rich consumers aged from 55 to 70 years living in the southern and east regions of China. In order to capture the potential demand, two competitive strategies are suggested to be applied by Mantero Company, which are cost leadership and focus differentiation strategy.